Impact of Technostress and Digital Health Awareness on Academic Burnout: Examining the Mediating Role of Sleep Quality among University Students (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2025)
In the era of digitalization, university students are becoming affected more and more The rapid digitalization of higher education has increased reliance on technology but also introduced psychological and behavioral challenges such as technostress, poor sleep, and burnout. This study investigated the effects of technostress and digital health awareness (DHA) on academic burnout among university students, with sleep quality examined as a potential mediator. Grounded in Cognitive Load Theory and the Job Demands–Resources (JD-R) model, a cross-sectional design was employed with 400 students from the University of Sargodha. Data were collected using validated instruments: the Technostress Scale, Digital Health Awareness Scale, Pittsburgh Sleep Quality Index (PSQI), and Maslach Burnout Inventory–Student Survey (MBI-SS). Correlation and regression analyses showed that technostress was positively associated with academic burnout and negatively associated with sleep quality. In contrast, DHA was positively associated with sleep quality and negatively associated with burnout, reflecting a protective effect. Mediation analysis using PROCESS Macro (Model 4) indicated that sleep quality partially mediated the relationship between technostress, DHA, and burnout. These findings suggest that while technostress intensifies burnout, awareness of digital health practices can reduce its impact, both directly and indirectly. The study highlights the importance of integrating digital wellness education and sleep hygiene programs into higher education to safeguard student mental health and academic success.